Hermesorchestia alastairi gen. et sp. nov. from Australia (Talitridae: Senticaudata: Amphipoda: Crustacea) - Hughes, Lauren Elizabeth; Lowry, James Kenneth (Zootaxa, 2017)
The new talitrid amphipod genus Hermesorchestia is established for one new species from Australia, H. alastairi, common to the beaches of Tasmania. Hermesorchestia gen. nov. is typified by the sexually dimorphic males which have palmate lobes on the carpus and propodus of gnathopod 1, a three dimensional merus article on pereopod 7 and expanded posterior margin of pereopod 7 carpus. Other characters which define H. alastairi gen. et sp. nov. are the male pereopod 6 expanded merus and carpus, pereopod 7 basis posterior expansion, merus shape both medial and facial, carpus posterior expansion and the shape and setation of the telson. Hermesorchestia alastairi gen. et sp. nov. is a documented burrower (sand-hopper), living in sand dunes above the high water mark.